Banking under pressure : breaking the chains - Clarke, Tim; Vincent, William (London Butterworths, 1989)
The revolutionary deregulation of the banking industry - the 'silent big bang' - initiated by Sir Geoffrey Howe's first budget, is taken as a starting point for this fascinating analysis of the UK banking industry as it faces up to a period of still greater upheaval.
Includes index
osc 25/4/17
Loans
Keywords: Banks and banking; Banking under pressure